Measuring Primary Health Care Clinicians’ Skills for Depression Management - Martínez, Pablo; Rojas, Graciela; Martínez, Vania; Marín, Rigoberto; Cornejo, Juan P.; Gómez, Víctor (Frontiers in Psychiatry, 2019)
1.1. Introduction Primary health care clinicians play an important role in the management of depression. Thus, it is very important to have a valid and reliable assessment of the competences needed to manage depression in primary health care, with the use of clinical simulation providing such an opportunity. 1.2. Objective The present study describes the assessment of primary health care clinicians’ depression-related skills through a series of objective structured clinical examination stations. 1.3. Material and Methods Clinicians from multi-professional teams for the management of depression at two primary health care clinics in Santiago, Chile, went through seven objective structured clinical examination stations, lasting 10 to 20 minutes each, to assess their depression-related skills. The clinical and communicative skills measured were in accordance with clinical guidelines. Standardized patients portrayed cases usually encountered in clinical practice, while expert raters evaluated clinicians’ performance with standardized checklists. 1.4. Results Psychosocial clinicians performed better than biomedical clinicians in the assessed skills. The most notable results were as follows: a high level of accomplishment in the relationship with patient, medical anamnesis, health checkup, and lab test requests; heterogeneous performance in patient management according to screening results, feedback to the patient, and registration in clinical records; and major deficiencies in the differential diagnosis of bipolar disorder. 1.5. Discussion The objective structured clinical examinations administered provided an opportunity to perform an in-depth examination of the depression-related skills of primary health care clinicians, where flaws in the screening and diagnosis procedures used by biomedical clinicians were detected. Given the significant involvement of these types of clinicians in depression management, undergraduate-level and continuing health education opportunities are needed.